Cross-Linking Assisted Infection Reduction (CLAIR): A Randomized Clinical Trial Evaluating the Effect of Adjuvant Cross-Linking on Bacterial Keratitis. Issue 7 (July 2021) - Prajna, N. Venkatesh; Radhakrishnan, Naveen; Lalitha, Prajna; Rajaraman, Revathi; Narayana, Shivananda; Austin, Ariana F.; Liu, Zijun; Keenan, Jeremy D.; Porco, Travis C.; Lietman, Thomas M.; Rose-Nussbaumer, Jennifer
Abstract : Purpose: To determine whether there is a benefit to adjuvant corneal cross-linking (CXL) for bacterial keratitis. Methods: This is an outcome-masked, randomized controlled clinical trial. Consecutive patients presenting with a smear-positive bacterial ulcer at Aravind Eye Hospitals at Madurai, Pondicherry, and Coimbatore in India were enrolled. Study eyes were randomized to topical moxifloxacin 0.5% or topical moxifloxacin 0.5% plus CXL. The primary outcome of the trial was microbiological cure at 24 hours on repeat culture. Secondary outcomes included best spectacle corrected visual acuity at 3 weeks and 3 months, percentage of study participants with epithelial healing at 3 weeks and 3 months, infiltrate and/or scar size at 3 weeks and 3 months, 3-day smear and culture, and adverse events. Results: Those randomized to CXL had 0.60 decreased odds of culture positivity at 24 hours (95% confidence interval [CI]: 0.10–3.50; P = 0.65), 0.9 logarithm of the minimum angle of resolution lines worse visual acuity (95% CI: −2.8 to 4.6; P = 0.63), and 0.41-mm larger scar size (95% CI: −0.48 to 1.30; P = 0.38) at 3 months. We note fewer corneal perforations or need for therapeutic penetrating keratoplasty in the CXL group. Conclusions: We were unable to confirm a benefit to adjuvant CXL in the primary treatment of moderate bacterial keratitis. However, CXL may reduce culture positivity and complication rates; therefore, a larger trial to fully evaluate this is warranted. Trial Registration: NCT02570321. Abstract : Supplemental Digital Content is Available in the Text.